Classification of high‐grade cervical intraepithelial neoplasia by p16(ink4a), Ki‐67, HPV E4 and FAM19A4/miR124‐2 methylation status demonstrates considerable heterogeneity with potential consequences for management - Vink, Frederique J. (Int J Cancer, 2021)
High‐grade cervical intraepithelial neoplasia (CIN2 and CIN3) represents a heterogeneous disease with varying cancer progression risks. Biomarkers indicative for a productive human papillomavirus (HPV) infection (HPV E4) and a transforming HPV infection (p16(ink4a), Ki‐67 and host‐cell DNA methylation) could provide guidance for clinical management in women with high‐grade CIN. This study evaluates the cumulative score of immunohistochemical expression of p16(ink4a) (Scores 0‐3) and Ki‐67 (Scores 0‐3), referred to as the “immunoscore” (IS), in 262 CIN2 and 235 CIN3 lesions derived from five European cohorts in relation to immunohistochemical HPV E4 expression and FAM19A4/miR124‐2 methylation in the corresponding cervical scrape. The immunoscore classification resulted in 30 lesions within IS group 0‐2 (6.0%), 151 lesions within IS group 3‐4 (30.4%) and 316 lesions within IS group 5‐6 (63.6%). E4 expression decreased significantly from CIN2 to CIN3 (P < .001) and with increasing immunoscore group (P (trend) < .001). Methylation positivity increased significantly from CIN2 to CIN3 (P < .001) and with increasing immunoscore group (P (trend) < .001). E4 expression was present in 9.8% of CIN3 (23/235) and in 12.0% of IS group 5‐6 (38/316). Notably, in a minority (43/497, 8.7%) of high‐grade lesions, characteristics of both transforming HPV infection (DNA hypermethylation) and productive HPV infection (E4 expression) were found simultaneously. Next, we stratified all high‐grade CIN lesions, based on the presumed cancer progression risk of the biomarkers used, into biomarker profiles. These biomarker profiles, including immunoscore and methylation status, could help the clinician in the decision for immediate treatment or a “wait and see” policy to reduce overtreatment of high‐grade CIN lesions.